Seat Pressure Distribution Characteristics During 1 Hour Sitting in Office Workers With and Without Chronic Low Back Pain - Nipaporn Akkarakittichoke; Prawit Janwantanakul (Elsevier, 2017)
Background: Low back pain (LBP) is a major problem for office workers. Individuals adopting poor postures during prolonged sitting have a considerably increased risk of experiencing LBP. This study aimed to investigate seat pressure distribution characteristics, i.e., average pressure, peak pressure ratio, frequency of postural shift, and body perceived discomfort (BPD), during 1 hour of sitting among office workers with and without chronic LBP. Methods: Forty-six participants (chronic LBP=23, control=23) typed a standardized text passage at a computer work station for an hour. A seat pressure mat device was used to collect the seat pressure distribution data. Body discomfort was assessed using the Body Perceived Discomfort scale. Results: Office workers with chronic LBP sat significantly more asymmetrically than their healthy counterparts. During 1-hour sitting, all workers appeared to assume slumped sitting postures after 20 minutes of sitting. Healthy workers had significantly more frequent postural shifts than chronic LBP workers during prolonged sitting. Conclusion: Different sitting characteristics between healthy and chronic LBP participants during 1 hour of sitting were found, including symmetry of sitting posture and frequency of postural shift. Further research should examine the roles of these sitting characteristics on the development of LBP.